PENGUATAN IMPLEMENTASI KURIKULUM MERDEKA BELAJAR-KAMPUS MERDEKA (MBKM) DI UNIVERSITAS NEGERI MEDAN - Frisnoiry, Suci; Sinaga, Fajar Apollo; Siregar, Tiur Malasari; Saputra, Kana; Ramadhan, Taufiq (Jurnal Pendidikan Matematika Malikussaleh, 2025)
This study aims to evaluate the effectiveness of strengthening the implementation of the Independent Learning-Independent Campus (MBKM) Curriculum at Universitas Negeri Medan (Unimed). The research method employed is a qualitative-descriptive approach through observation, interviews, and document analysis. The findings indicate an improved understanding among lecturers regarding the MBKM concept, a more systematic curriculum document development, and enhanced collaboration with industry partners. Additionally, a more structured monitoring and evaluation system has been successfully developed to ensure the sustainability of the program. These findings suggest that the MBKM program can enhance the quality of higher education and better prepare graduates to face the challenges of the job market. Recommendations are provided to improve faculty training, digitize the MBKM system, and conduct periodic evaluations to align the curriculum with industry needs and national policies